Geology of the Carpathian region - FoÌˆldvary, G.Z (World Scientific, 1988)
It is aimed to pave the way for global geologists to examine this tectonically complex and key area and to build up a clear picture about its origin, evolution and structure. It provides factual geological material for plate tectonicians to work on and to derive basic information from. Since it is intended to be comprehensive, it will also be a useful source material for professional geologists and specialists in the earth sciences.; Includes bibliographies and index